Vinasse affects the formation of iron plaque on roots of Acorus calamus and immobilization of lead, cadmium, copper, zinc by this plant. (December 2020) - Ma, Huanhuan; Gao, Feng; Fan, Xiangyang; Cui, Bingjian; Liu, Chuncheng; Cui, Erping; Zhang, Zulin; Hu, Chao; Mo, Yu
Graphical abstract: Highlights: Vinasse promoted formation of iron plaque under high level of Pb, Cd, Cu, Zn. Vinasse promoted root growth of Acorus calamus. Iron plaque facilitated transfer of Cd and Zn to the aboveground part. Pb was mainly stored in iron plaque, while Cu was mainly stored in roots. Vinasse effectively removed Pb-Cd-Cu-Zn in co-contaminated wastewater. Abstract: Iron plaque (IP) on root surface has a significant effect on uptake and accumulation of heavy metals by wetland plants, however, the role of vinasse in modulating the relevant process still remains unclear. Present study hypothesizes vinasse at appropriate addition could promote IP formation and lead (Pb), cadmium (Cd), copper (Cu) and zinc (Zn) removal by Acorus calamus in constructed wetlands (CWs). For that purpose, 0, 0.2% and 0.4% addition of vinasse was applied in lab-scale CWs planted with A. calamus which were conducted with low and high concentration of Pb, Cd, Cu and Zn wastewater, respectively. Results indicated that increase of heavy metals concentration promoted root oxidation activity and the expression of heavy metal transport genes were increased, which was the reason that vinasse promoted the formation of IP under high concentration of Pb, Cd, Cu and Zn, while inhibited under low concentration of Pb, Cd, Cu and Zn. The change of IP affected by vinasse had a strong effect for uptake and accumulation of Pb, Cd, Cu and Zn by A. calamus . IP facilitated the transfer of Cd and Zn to the aboveground part. Pb was mainly stored in IP, while Cu was mainly stored in the root. Redundancy analysis (RDA) showed IP content and Pb, Cd, Cu, Zn contents in IP played a decisive role in the heavy metal uptake and accumulation in A. calamus . Therefore, vinasse has potential to be used in CWs to assist wetland plants in removing Pb-Cd-Cu-Zn co-contaminated wastewater.